BASIC, decision making on the microcomputer - Ginter, Peter M.; Rucks, Andrews C. (New York : Random House Business Division, 1985)
Computer programming is a tool used in decision making and problem solving. Fundamental to computer programming is the ability to conceptualize a situation, to understand information requirements, to develop methodology, and to make sense of the results of the selected method-in other words, the ability to think.
Part One. An introduction to basic programming -- Part Two. Programming essentials -- Part Three. Iteration and arrays -- Part Four. Advanced applications topics -- Part Five. Appendices.
Includes bibliographical references and index.
Keywords: BASIC (COMPUTER PROGRAM LANGUAGE)